Answer:
8x - 4y + 12
Step-by-step explanation:
-2(-4x + 2y - 6)
(-2)(-4x) + (-2)(2y) + (-2)(-6)
(2 * 4x) - (2 * 2y) + (2 * 6)
8x - 4y + 12
Answer:
There is information missing from this question. Cannot be answered in its current form.
Step-by-step explanation:
The statement is true, but the inverse is false.
Eq1) 2r+2s=50
eq2) 2r-s=17
solve for s in equation2 (eq2)
-s=17-2r
s=-17+2r
Substitute s into equation1 (eq1)
2r+2(-17+2r)=50
2r-34+4r=50
6r-34=50
6r=50+34
6r=84
r=14
Substitute into either equation and solve for s
2(14)-s=17
28-s=17
-s=17-28
-s=-11
s=11